Optimal dose-fractionation schedule of palliative radiotherapy for patients with bone metastases: a protocol for systematic review and network meta-analysis. Issue 1 (6th January 2020) - Tang, Xiaofang; Hu, Qiancheng; Chen, Ye; Wang, Xin; Li, Xiaofen; Cheng, Ke; Cao, Dan
Abstract : Introduction: The optimal dose-fractionation schedule of palliative radiotherapy has been debated in patients with bone metastases. Our objective is to comprehensively compare multiple fraction schedules with single fraction radiotherapy in terms of efficacy and toxicities by performing a systematic review and network meta-analysis. Methods and analysis: Electronic searches of titles/abstracts of palliative radiotherapy for bone metastases will be performed, using PubMed, Cochrane Library, Embase, c linical trials, American Society for Therapeutic Radiology and Oncology and European Society of Radiotherapy and Oncology. The primary outcome of interest is the incidence of skeletal-related event following palliative radiotherapy for bone metastases in prospective studies. The risk of bias and quality of evidence will be evaluated based on Cochrane Collaboration's tool and Grades of Recommendation, Assessment, Development and Evaluation in the network meta-analysis. We will conduct subgroup analysis and sensitivity analysis regardless of heterogeneity estimates. Ethics and dissemination: This study will synthesise the evidence regarding dose-fractionation schedule of palliative radiotherapy in patients with bone metastases. We hope the findings from this study will help clinicians and patients select optimum palliative radiotherapy by identifying the optimal dose-fractionation schedule of palliative radiotherapy with the most value in terms of patient-important outcomes. The evidence obtained from network meta-analysis will help to guide head-to-head research in the future. The results will be disseminated through international conference reports and peer-reviewed manuscripts. Ethics review board is not required for this network meta-analysis. PROSPERO registration number: CRD42019135195.